Incidental Renal Artery Stenosis amongst a Cohort of Hypertensive Patients Undergoing Coronary Angiography: An Analytical Cross-Sectional Study : Incidental Renal Artery Stenosis: Hypertensive Patients Undergoing Coronary Angiography - Din, Zuhoor Ud; Ishaq, Sheeba; Ibrahim, Jahanzeb; Khan, Sara Daud; Gul, Hina; Noor, Sahib; Khan, Wassay Hassan (Pakistan Journal of Health Sciences, 2026)
There has been less research on accidental RAS in patients with hypertension who have received coronary angiography. Objectives: To determine the prevalence rate of incidental renal artery stenosis (IRAS) in patients having coronary angiography. Methods: This analytical cross-sectional study was conducted at Khyber Teaching Hospital for six months between 1st April 2025 and 30th September 2025. Consecutive sampling was used to enroll 139 hypertensive patients under diagnostic coronary angiography as participants. Findings of coronary angiography and incidental evaluation of the renal artery were recorded, with stenosis of ≥50% seen as IRAS. The analysis of data was done with SPSS version 25.0. Odds ratios were estimated at 95% confidence intervals using univariate analysis. Results: Incidental renal artery stenosis was observed in 18.0% of patients, and in 13.7% and 4.3%, respectively, bilateral and unilateral renal artery stenosis. IRAS was significantly correlated with longer hypertension period and high serum creatinine (p<0.05). Conclusions: Nearly one-fifth of hypertension patients who had coronary angiography had incidental renal artery stenosis, most of which were unilateral. Chronic hypertension and high creatinine were identified as some of the most important associated factors, and it is important to evaluate renal arteries when the coronary arteries should be evaluated to be able to assess the cardiovascular and renal risks.